2015
DOI: 10.1371/journal.pone.0141392
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Reduces Desmoplasia in Pancreatic Cancer by Reprogramming Stellate Cells and Tumor-Associated Macrophages

Abstract: BackgroundPancreatic ductal adenocarcinoma (PDAC) is a highly desmoplastic tumor with a dismal prognosis for most patients. Fibrosis and inflammation are hallmarks of tumor desmoplasia. We have previously demonstrated that preventing the activation of pancreatic stellate cells (PSCs) and alleviating desmoplasia are beneficial strategies in treating PDAC. Metformin is a widely used glucose-lowering drug. It is also frequently prescribed to diabetic pancreatic cancer patients and has been shown to associate with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
94
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(104 citation statements)
references
References 94 publications
7
94
2
Order By: Relevance
“…Incio and colleagues report that activating AMPK signaling pathways with metformin is able to reduce the M2 markers Arg1 and IL-10 in TAMs isolated from orthotopic models of mouse PDAC. 44 This is associated with an alleviation of desmoplasia at the tumor site, and reduction of both EMT and systemic metastasis. 44 These results point toward possible AMPK signaling in Panc1 and MiaPaCa2-TAMs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Incio and colleagues report that activating AMPK signaling pathways with metformin is able to reduce the M2 markers Arg1 and IL-10 in TAMs isolated from orthotopic models of mouse PDAC. 44 This is associated with an alleviation of desmoplasia at the tumor site, and reduction of both EMT and systemic metastasis. 44 These results point toward possible AMPK signaling in Panc1 and MiaPaCa2-TAMs.…”
Section: Discussionmentioning
confidence: 99%
“…44 This is associated with an alleviation of desmoplasia at the tumor site, and reduction of both EMT and systemic metastasis. 44 These results point toward possible AMPK signaling in Panc1 and MiaPaCa2-TAMs. However, detailed exploration into the signaling pathways involved in these TAMs is beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 The effect of metformin is hypothesized to be the result of decreased insulin-like growth factor signaling as well as the halting of desmoplastic cell growth and division. 12 Specifically, metformin targets the AMP-activated protein kinase/mechanistic target of rapamycin (AMPK/mTOR) pathway and induces cell cycle arrest, preventing tumor progression. 13 While previous studies have suggested that metformin use in patients with neoplastic disease may lead to a longer overall survival and a lower risk of death, data on patients with pancreatic cancer have been limited.…”
Section: Introductionmentioning
confidence: 99%
“…Joao Incio t al. e [13] found that metformin alleviated the fibro-inflammatory microenvironment in obese/diabetic individuals with PC by reprogramming PSCs. Wanxing Duan et al [17] found that metformin induction of AMPK activation represented a novel therapeutic approach for treating advanced PC through desmoplasia suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin could also inhibit hepatocellular carcinoma angiogenesis by targeting HSCs through the AMPK pathway [12]. However, the influence of metformin on PSCs is not well known [13].…”
Section: Introductionmentioning
confidence: 99%